Histopathological Study of Escherichia coli O157:H7 Isolated from Children with Bloody Diarrhea in Mice - Al-Jobory, Mohamed B; Al-Thwaini, Amina N; Najeeb, Laith M (Al-Nahrain Journal of Science, 2018)
Escherichia coli O157:H7 is well documented with Shiga toxin–producing serotypes of E. coli. Infection with this type of pathogenic bacteria may lead to hemorrhagic diarrhea and kidney failure. This study was carried out to detect the pathogenicity of E. coli O157:H7 isolated from patients with bloody diarrhea. A total of 200 bloody diarrhea samples were collected from children of both sexes, with age between 3 to10 years in the period from beginning of September to the end of December 2016 in Al-Eskan Pediatrics Hospital and Children Safe Hospital (Baghdad/Iraq). The samples were cultured aerobically on enrichment and selective media, then the isolates were identified by Vitek 2 and they were confirmed by latex agglutination test. Eight isolates were diagnosed and identified as Escherichia coli O157:H7. The pathogenicity of the stool recovered isolates were study to recognize the alterations in some organs of mice after experimentally infected with this pathogen. Twelve mice provided by animal house of AL-RAZI center in Baghdad, divided into two groups each group consist of 6 mice. The first group injected with 0.2 ml of de-ionized water and left as control group, whereas the second group infected orally with 0.2 ml of 1.8x106cfu/ml. The animals of two groups sacrificed 24-48 hours post infection. The histopathological examination of intestine for infected mice showed infilteration of inflammatory cells, focal lining epithelial stratification, with multiple layer basal lamina degeneration, then distention of villi appeared with increase inflammatory cells infiltration. The liver showed accumulation of lymphocyte, hemorrhage in central vein with sinuses expansion and, hepatocyte cells showed, degeneration, increase nuclear size and increase hyperchromasia with irregular chromatin distribution. The histopathological examinations of the control group were naïve.